Cost-Effective Arduino-Based RFID Automated Cage Door and Pet Tagging with GPS Tracker using Peer-to-Peer LoRa WAN - Francis, Imelda; Mohd Shah, Shaharil (Journal of Electronic Voltage and Application, 2022)
In this modern era, there is a lot of technology improvement in pet cages and pet tagging. Manually operating a pet cage might not be really efficient for the modern world. Moreover, when the pets go missing it is always a hassle to know about their whereabouts. Hence, this cage is able to sense the pet when it is nearby by detecting the RFID embedded in the pet tag. If the pet goes missing or is outside the cage’s vicinity, the owners should be able to obtain the pets location by using the GPS module with peer-to-peer LoRa WAN which is embedded in the pet tag. Previous research has primarily relied on either an automated pet cage or a GPS tracker with a short range. In this work, the RFID and GPS system implements peer-to-peer LoRa WAN in the pet tag which is able to unlock the pet cage and also help the owner to track the pet’s location via a web-based maps by inserting the coordinates (latitude and longitude) obtained. The RFID RC522 is integrated with the Arduino UNO for the Arduino-based automatic pet cage. As for the peer-to-peer LoRa WAN GPS tracker, the RFM95W LoRa shield integrated with the Arduino UNO is used as the transmitter and receiver. The transmitter of LoRa WAN shield has a GPS tracker (NEO-6M) and the receiver LoRa WAN has an LCD display, so that the owner can obtain the coordinates of the pet. It is shown from this work that the LoRa WAN can transmit signals within a coverage area of up to 10 km